IMPLEMENTASI PENDIDIKAN KARAKTER SISWA PERGURUAN ISLAM AN-NIZAM MEDAN - Hasnan Syarief (EDUTECH, 2017)
Purpose of Research Singer is to know the Process of Character Education, to know  Values Character, to know identify factors inhibiting hearts Implementation Support And Character Education in Private Islamic schools in the city of Medan. The singer is a qualitative research operates. Population Research is a college student  Islamic An-Nizam Medan (total sampling), an instrument which was used Form questionnaire. Research shows that teachers and students Already Implementing Character Education Under with draft which is dictated by Islamic An-Nizam college Medan. And have a significant influence Which Character Against Students. Character-value value lead with Diversified approach to character education, which in the mix on different Learning and extracurricular activities.Keywords: Implementation, Character, results of learning, extracurricular